The maternal U1 haplogroup in the Koraga tribe as a correlate of their North Dravidian linguistic affinity - Sequeira, Jaison Jeevan; Vinuthalakshmi, Kadengodlu; Das, Ranajit; van Driem, George; Mustak, Mohammed S. (Frontiers in Genetics, 2024)
The Koraga tribe are an isolated endogamous tribal group found in the southwest coastal region of India. The Koraga language shares inherited grammatical features with North Dravidian languages. To seek a possible genetic basis for this exceptionality and understand the maternal lineage pattern, we have aimed to reconstruct the inter-population and intra-population relationships of the Koraga tribal population by using mtDNA markers for the hypervariable regions along with a partial coding region sequence analysis. Amongst the 96 individuals studied, we observe 11 haplogroups, of which a few are shared and others are unique to the clans Soppu, Oṇṭi and Kuṇṭu. In addition to several deep rooted Indian-specific lineages of macrohaplogroups M and U, we observe a high frequency of the U1 lineage (~38%), unique to the Koraga. A Bayesian analysis of the U1 clade shows that the Koraga tribe share their maternal lineage with ancestral populations of the Caucasus at the cusp of the Last Glacial Maximum. In other words, our study suggests that the U1 lineage found in the Indian subcontinent represents a remnant of a post-glacial dispersal. The presence of West Asian U1 when viewed along with historical linguistics leads us to hypothesise that Koraga represents a mother tongue retained by a vanquished population group that fled southward at the demise of the Indus civilisation as opposed to a father tongue, associated with a particular paternal lineage.